SCIENTIFIC CHARACTERISTIC OF ACADEMIC TEXTS A STUDY OF SYSTEMIC FUNCTIONAL LINGUISTICS - Salam, Abdul; Mahfud, Mahmudah; Nurhusna, Nurhusna (Universitas Negeri Makassar, 2018)
Systemic functional linguistics is related to a sign system that can be used to trace the scientific characteristic of academic texts. This study aimed at describing academic texts covering four technical terms: (1) simple, (2) dense, 3) objective, and (4) directness. Data analysis was done through three stages: (a) data reduction, (b) data display, (c) data verification/conclusion. The findings of the study indicate that there are 129 sentences consisting of 53 simple sentences with a percentage of 41, 09%, 37 complex sentences with a percentage of 28.68% and 39 single sentences with a percentage of 30.23%. Thus, it can be concluded that the results of this research show that scientific characteristics of academic texts from systemic functional linguistics perspectives containing: (1) simple sentence structure, (2) dense information, (3) objective definition and identification, and (4) direct presentation. Based on the result of the research, it is suggested to conduct further research on academic texts from holistic approach that uncovers large number of texts from different resources. In addition, it is important to explore the quality of academic text from systemic functional lens